Digital appendix: Structural cerebrocortical changes in ageing and chronic neuropathic pain: a mouse study correlating magnetic resonance imaging and in vivo two-photon microscopy - Asan, Livia (Universität, 2023)
This is the digital appendix to the dissertation by Livia Asan, titled "Structural cerebrocortical changes in ageing and chronic neuropathic pain - a mouse study correlating magnetic resonance imaging and in vivo two-photon microscopy", at the Faculty of Medicine, Heidelberg, Ruprecht-Karls-University.
Gesehen am 04.10.2023
Keywords: Forschungsdaten; Datenbank